Pengaruh Copywriting Dan Desain Kemasan Minuman Oatside Dalam Membentuk Brand Awareness Produk Minuman Kemasan Oatside - Ardita, Yasmin Elysia (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the influence of packaging design and copywriting on the development of brand awareness for the Oatside beverage product. Within a highly competitive market saturated with visual and verbal marketing strategies, Oatside stands out through its distinctive packaging design and witty, communicative copywriting. The research adopts a quantitative explanatory survey method involving 113 respondents aged ≥ 17 years who have seen or consumed Oatside. Data were collected through online and offline questionnaires and analyzed using validity tests, reliability tests, Pearson correlation, multiple regression, and cross-tabulation via SPSS software. The findings indicate that both packaging design and copywriting significantly influence brand awareness, with copywriting being the more dominant variable. The correlation test also reveals a strong positive relationship between the two independent variables, highlighting the importance of consistent visual and verbal messaging. Additionally, the 21–30 year age group emerges as the most exposed and brand-aware segment. The implications underscore the strategic role of integrating visual and narrative elements in packaging as an effective brand communication tool to build strong brand equity.